Conhecimento dos Farmacêuticos da atenção primária à saúde de Belo Horizonte sobre Tuberculose - Joyce Laura Moreira (2014)
The pharmacist is an important professional when referring to information on drugs, and that this professional be prepared for their duties, it should be a source of accurate and reliable information. Among all of the pharmacist, the professional has an important role in the treatment of diseases and clinical conditions common in primary health care, including tuberculosis (TB), aiding in treatment adherence. The pharmacist has the responsibility to constantly monitor the patient with TB, to evaluate the use of medication, prevent wrong use and also educate the public and inform professionals of Family Health Teams (FHT) on the rational use of medicine through actions governing the prescribing, dispensing and use of medication. TB remains a disease of public health relevance and adherence to treatment is a problem that needs to be constantly addressed. The objective of this study was to assess the knowledge regarding different aspects of tuberculosisby pharmaceutical professionals working in Primary Health care in Belo Horizonte, Minas Gerais. It is a cross-sectional study involving 53 pharmacists who work in NASFs linked to Health Centers of the Municipality of Belo Horizonte, by applying semi-structured questionnaire, self-administered, pre-tested. The variables measured results were arranged in percentage of correct answers on TB, TDO, diagnosis and treatment. Most pharmacists were female, mean age 33.5 years, predominantly formed between 2006 and 2011 and less than two years working in the PBHs APS. With regard to knowledge, the mean score was 79.6%, the TDO domain to more correct and the diagnosis domain the lowest average. The level of knowledge was categorized as above or below the average for comparison purposes as the characteristics of respondents. Statistically significant associations were observed between the domain "diagnosed" with not having postgraduate, working time in the APSs PBH and time of conducting training on TB provided by PBH. Was also found statistically siginificante association between the domain "Treatment" and the perception of knowledge gained about TB in the training offered by PBH. We understand that pharmacists who work in the APS Belo Horizonte showed a good level of knowledge regarding different aspects of TB, with gaps, mainly in the field of knowledge "treatment. Recognizing the important role of the pharmacist in monitoring the patient with TB, it points to the crucial need for continuing education of these professionals.